Menggunakan Paradigma Studi Kasus Kualitatif Interpretatif Online dan Offline Untuk Memahami Efektivitas Penerapan E-Procurement - Nurdin Nurdin; Sagaf S. Pettalongi (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
The presence of social media allows researchers to consider new data collection and triangulation strategies. Positivist researchers take advantage of the internet's presence as a medium for collecting data. Meanwhile, interpretive qualitative researchers have not utilized the potential provided by social media to enrich data collection in order to deepen understanding of a topic being researched. By using the case of the effectiveness of the application of e-procurement in a district, the researcher conducted face-to-face interviews (offline) and also observed discussions on social media and content sharing about the implementation and use of government e-procurement in a district. This study uses an interpretative qualitative paradigm to describe how social media exchanges, uploads, and conversations can be used as a means of collecting data in interpretive qualitative research. The results of this study indicate that social media observation can be used as a research tool to increase understanding of a topic being studied and also as a triangulation medium. This study also proves that the use of social media in interpretive studies can reduce challenges in informant recruitment, access to research sites, and reduce bias in interviews. This research contributes to the understanding of a research topic using data from two environments.Keywords:Social media, interpretif study, e-procurement effectiveness, research paradigm